Growth performance and intestinal histomorphology of Nile tilapia juveniles fed probiotics - doi: 10.4025/actascianimsci.v35i4.18610 - Ivan Bernardoni Nakandakare; Marina Keiko Pieroni Iwashita; Danielle de Carla Dias; Leonardo Tachibana; Maria José Tavares Ranzani-Paiva; Elizabeth Romagosa (Acta Scientiarum. Animal Sciences, 2013)
The objective of this study was to assess the growth performance and thehistomorphometric characterization of the middle intestine of GIFT strain Nile tilapia, Oreochromis niloticusjuveniles fed probiotics, added either before or after the feed processing. The experimental design wascompletely randomized, with five treatments and five replications: pelleted feed without any probiotic;pelleted feed with inclusion of probiotic before the processing; pelleted feed with inclusion of probioticafter the processing; extruded feed without any probiotic and extruded feed with inclusion of probioticafter the processing. Two hundred and fifty juveniles were distributed in 25 aquaria (20L) and fed for 63days. Differences in the mean values of total weight were found at the end of the experiment. After 42 daysof feed intake, significant differences in feed conversion were verified for treatments with extruded dietswhen compared to the pelleted ones. The fishes fed diets supplemented with probiotic presented increasein the thickness of the epithelium of the intestine. The best zootechnical performance was observed in theextruded diet supplemented with probiotic added after the feed processing. The inclusion of 4.0 x 108 CFU g-1 ofBacillus subtilis and 4.0 x 108 CFU g-1 of Bacillus toyoi in both the pelleted and the extruded diets promoted anincrease in the thickness of the epithelial layer of the middle intestine.